2021
DOI: 10.1002/prep.202000327
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Use of Burning Rate Suppressants in AP‐Based Composite Propellants

Abstract: Ammonium perchlorate (AP) is the most widely used oxidant in composite propellants. Propellants based on AP usually have a high burning rate, but in some applications, it is necessary to have a slower burning rate. The functional additives, which can reduce the burning rate of propellants, were named coolants, burning rate suppressants (BRSs), burning rate depressants, or burning rate inhibitors. This paper introduced different types of BRSs, such as amide-based compounds, cyclic azines, quaternary ammonium sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…No matter for the HTPB/AP/Al propellants or HTPB/AP/RDX/Al propellants, the HTPB/DDI curing system makes the burning rates of the propellant decrease without adding any additives lowering the burning rates. It is worth noting that for the three propellants in Figures 9 and 11, in the pressure range around 15 MPa, the burning rate-pressure exponents of the propellants will decrease in different degrees, which may be related to the decrease of pure AP burning rates in this pressure range [42][43][44][45][46]. Atwood et al [47] studied the relationship between the burning rate of AP and pressure in detail.…”
Section: Combustion Properties Of the Htpb/ap/rdx/al Propellantsmentioning
confidence: 98%
“…No matter for the HTPB/AP/Al propellants or HTPB/AP/RDX/Al propellants, the HTPB/DDI curing system makes the burning rates of the propellant decrease without adding any additives lowering the burning rates. It is worth noting that for the three propellants in Figures 9 and 11, in the pressure range around 15 MPa, the burning rate-pressure exponents of the propellants will decrease in different degrees, which may be related to the decrease of pure AP burning rates in this pressure range [42][43][44][45][46]. Atwood et al [47] studied the relationship between the burning rate of AP and pressure in detail.…”
Section: Combustion Properties Of the Htpb/ap/rdx/al Propellantsmentioning
confidence: 98%
“…27 It has been shown that the alkaline earth metal ions can react with AP (or HClO 4 ) to form more stable compounds such as Ca(ClO 4 ) 2 , thereby prohibiting the thermal decomposition of AP. 28 Although nano TAGP or TAGP-Ms have been used in solid propellants, there is still a lack of systematic research on the molecular weight, thermal reactivity, and cross-link reaction process of TAGP. Therefore, this study focused on obtaining in situ doped layers of TAGP in nitramine oxidizers through the spray drying method.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As an alternative method, the TAGP-Ms containing K + , Ba 2+ , and Ca 2+ were prepared as novel energetic burn rate inhibitors . It has been shown that the alkaline earth metal ions can react with AP (or HClO 4 ) to form more stable compounds such as Ca­(ClO 4 ) 2 , thereby prohibiting the thermal decomposition of AP …”
Section: Introductionmentioning
confidence: 99%
“…Composite solid propellants have attracted significant attention for their extensive use in rocket and missile engines. Composite solid propellants typically consist of oxidizers, polymeric binders, metal fuels, curing agents, combustion catalysts, plasticizers, and other components. Ammonium perchlorate (AP) is one of the most widely used oxidizers in composite solid propellants because of its high oxygen content and outstanding physical and chemical properties. In the presence of AP, the composite solid propellants show excellent combustion performance, storability, acceptable cost, and processability. The decomposition properties of AP directly affect the combustion performance of composite solid propellants, which strongly impacts the stability and survivability of the rocket and missile. Therefore, it is necessary to enhance the decomposition performance of AP.…”
Section: Introductionmentioning
confidence: 99%